2020
DOI: 10.1101/2020.03.18.20037846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neoadjuvant and Adjuvant Pembrolizumab in Resectable Locally Advanced, Human Papillomavirus-Unrelated Head and Neck Cancer: A Multicenter, Phase 2 Trial

Abstract: Background: Pembrolizumab improved survival of patients with recurrent or metastatic head and neck squamous-cell carcinoma (HNSCC). The aims of this phase 2 trial were to determine if pembrolizumab administered to patients with resectable locally advanced, human papillomavirus (HPV)-unrelated HNSCC would be safe, result in pathologic tumor response (pTR), and lower the relapse rate. Methods: Neoadjuvant pembrolizumab (200 mg) was administered 2-3 weeks before surgery. Resection of the primary tumor and involve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 28 publications
(58 reference statements)
3
19
1
1
Order By: Relevance
“…To date, two phase 2 studies evaluating neoadjuvant anti-PD-1 agents have shown antitumor activity in patients with resectable HNSCC, with clinical to pathological downstaging and PTR rates (defined as a reduction of viable tumor > 50%) ranging from 19% and 22% with one dose of pembrolizumab, to 69% and 40% with two doses of nivolumab, respectively. 18 32 Similar to what occurred in the recurrent/metastatic setting, PD-L1 expression seemed to enrich for responses in the pembrolizumab study, although this correlation was not observed in the nivolumab study. Anti-PD-1/PD-L1-based combinations with other immuno-oncology agents, targeted therapies or chemotherapy are currently being evaluated in the neoadjuvant space of this disease to increase tumor responses.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…To date, two phase 2 studies evaluating neoadjuvant anti-PD-1 agents have shown antitumor activity in patients with resectable HNSCC, with clinical to pathological downstaging and PTR rates (defined as a reduction of viable tumor > 50%) ranging from 19% and 22% with one dose of pembrolizumab, to 69% and 40% with two doses of nivolumab, respectively. 18 32 Similar to what occurred in the recurrent/metastatic setting, PD-L1 expression seemed to enrich for responses in the pembrolizumab study, although this correlation was not observed in the nivolumab study. Anti-PD-1/PD-L1-based combinations with other immuno-oncology agents, targeted therapies or chemotherapy are currently being evaluated in the neoadjuvant space of this disease to increase tumor responses.…”
Section: Discussionmentioning
confidence: 69%
“…Neoadjuvant anti-PD-1 therapy in patients with resectable HNSCC has been investigated in small studies showing promising antitumor activity with an overall safe toxicity profile, leading to ongoing large randomized trials (ie, NCT03765918). 17 18 However, about half of these patients did not respond to neoadjuvant anti-PD-1 therapy, thus, combination strategies using other immuno-oncology agents or targeted therapies such as antiangiogenic agents are under evaluation (NCT04199104 and NCT04675294). 19 20 MET, AXL and VEGF overexpression is associated with early nodal and distant metastasis as well as with mechanisms of resistance to radiation and systemic therapies in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these patients PD-1 blocking leads to long lasting responses [2]. Recently, the clinical use of checkpoint inhibitors is shifting towards early stages of OSCC treatment with the first results of successful neoadjuvant PD-1 inhibition being published [3,4] and currently evaluated in a large prospective study (KEYNOTE-689 study; NCT03765918).…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that a majority of the risk in these patients is derived from radiation treatment effect. Similarly, in a recently published phase 2 study of neo‐adjuvant/adjuvant pembrolizumab in HNSCC treated sequentially with RT followed by PD‐1, the rate of new hypothyroidism was 33% 24 . The development of anti‐thyroid antibodies may have provided some interesting insight as to the mechanisms of thyroid toxicity in RT + PD‐1 treated patients, but were rarely available in our patient cohort limiting this analysis.…”
Section: Discussionmentioning
confidence: 81%